PENGHILANGAN DETERJEN DAN SENYAWA ORGANIK DALAM AIR BAKU AIR MINUM DENGAN PROSES BIOFILTER UNGUN TETAP TERCELUP - Nusa Idaman Said (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
According to PDAM survey in Jakarta, Surabaya and other cities, surfacewater resources didn’t meet standard quality anymore for raw drinking water.Synthetic detergents, mostly anionic detergents have been widely used inIndonesia over past three decades, similar to its use in other developing countries, and residuals from such use have entered the country's riverine and estuarine systems. Detergent and other organic substance problems have become more seriuos especially in urban areas where the spread of sewerage systems are still low. According to this reason, it is important to develop low-cost technology to solve this problem such as developing biological treatment for removing detergents and organics.The present study describes the removal detergents and organic matter inriver water using submerged fixed bed biofilter with honeycomb tube plastic media. The experiments were operated by submerged fixed bed biofilter reactor using honeycomb plastic media continuously with size 21 cm x 30 cm x 59 cm, the total volume 372 litters. Results of experiments showed that using this method the removal efficiency of organic matter were affected by hydraulic retention time in reactor. The best conditions are achieved in aerobic tretment (Hydrolic retention time 4 hours) with the removal efficiency were 68,702% for organic materials,and 71,85% for detergent respectively.